The CEFR perspective on genre information in French for specific purposes textbooks - Jarc, Mojca (Linguistica (Ljubljana), 2014)
In the past twenty years, the results of genre-based studies have been introduced into programmes of languages for specific purposes and even genre-based approaches have been used to teach languages for specific purposes. At the same time, the CEFR has been recognised as an important tool and reference in the process of materials design. However, the relationship between these two powerful frameworks has not been fully explored. In this article, we aim to analyse this relationship in order to reveal how genre knowledge is presented through written texts and through tasks included in textbooks. Based on the results of qualitative text analysis, we argue that the integration of the CEFR and genre perspectives yields valuable information concerning the role of genres at different CEFR levels and in different domains. We offer an insight into the genre identities portrayed in French for Specific Purposes textbooks and identify the possible types of gaps that may arise when the user's professional identities are considered through the genres included in textbooks.
Keywords: Cadre européen commun de référence pour les langues; CECRL; français; francoščina; French; genres de texte; langue de spécialité; manuels; SEJO; Skupni evropski jezikovni okvir; strokovni jezik; tipi besedila; tuji jeziki; učbeniki; žanr